Impact of COVID-19 Pandemic on the Health of Preterm Infants in Iran - Mohammad Reza Zarkesh (Mashhad University of Medical Sciences, 2021)
Background: Coronavirus disease 2019 (COVID-19) directly increases the risk of preterm delivery. Furthermore, the COVID-19 pandemic may indirectly affect the health status of preterm infants. In the present study, several views have been mentioned regarding the negative effects of this viral disease on postnatal health that require much consideration. Methods: A related brief study was conducted in 2020. Previously published works have revealed several adverse effects of the COVID-19 pandemic on the health of preterm neonates.Results: Literature review has demonstrated that several policies have been implemented to protect newborns from the risk of infection in the neonatal intensive care units (NICU). Some of these policies are isolation of COVID-19 positive mothers, mother-infant separation, interruption in skin-to-skin contact and breastfeeding, restrictions associated with the presence of parents in the NICUs. Moreover, postponement of follow-up consultations and deficiency in healthcare services are other critical issues.Conclusion: Urgent measures seem to be implemented to protect preterm neonates and their parents from severe consequences. Some beneficial recommendations are providing adequate professional human resources in the NICUs, improving virtual communication for involving parents in NICU admissions and postnatal follow-up appointments, promoting exclusive breastfeeding for subjects without any contraindications, reminding vaccination schedule by calling or texting, reducing the family financial instability by governmental support, and improving mother-infant bonding with hand and respiratory hygienes.